Toxic Chemical Compounds of the Solanaceae - Pomilio, Alicia B. (2008)
The Solanaceae is comprised of some 2500 species of cosmopolitan plants, especially native to the American continent. They have great value as food, like the well-known potato, tomato and eggplants, and medicines, like species of Atropa, Withania and Physalis, but many plants of this family are toxic, and sometimes lethal to mammals, in particular to man. Some of them also produce hallucinations and perceptual changes. The toxic species of this family are characterized by the occurrence of a variety of chemical compounds, some of which are responsible for the toxicity and lethality observed after ingestion, while others are suspected to be toxic. In this review, the following toxic compounds belonging to different members of the Solanaceae family are described: Tropane alkaloids (Atropa, Datura, Hyoscyamus, Mandragora); pyrrolidine and pyrrolic alkaloids (Nierembergia, Physalis, Solanum); protoalkaloids (Nierembergia); glycoalkaloids (Lycopersicon, Solanum); nicotine (Nicotiana); cardenolides (Cestrum, Nierembergia); capsaicinoids (Capsicum); kaurene-type tetracyclic diterpenes (Cestrum); steroidal glycosides (Cestrum, Solanum); 1,25-dihydroxyvitamin D3 and vitamin D3 (Cestrum, Solanum, Nierembergia); and withasteroids, withanolides (Withania), and physalins (Physalis). Other bioactive chemical constituents of members of this family are sugar esters and lectins. Phenylpropanoids are not included in this paper.